Image process device and the operation method (2024)
본 발명은, 복수의 광을 각각 발산하는 복수의 광원, 피사체를 촬영한 제1 피사체 영상을 출력하는 카메라 및 상기 카메라의 셔터 노출 시간 동안, 상기 복수의 광원 각각을 복합 변조전달함수를 기반으로 설정한 광 코드 패턴 세트에 따라 제어하며, 상기 광 코드 패턴 세트에 의해 변조된 색상 채널별 점확산 함수에 따라 상기 제1 피사체 영상에서 모션블러가 제거된 제2 피사체 영상을 출력하는 제어부를 포함하는 영상 처리 장치를 제공한다. There is provided an image processing device including: a plurality of light sources each emitting a plurality of lights; a camera outputting a first subject image obtained by photographing a subject; and a control unit controlling each of the plurality of light sources according to an optical coded pattern set based on a complex modulation transfer function during a shutter exposure time of the camera, and outputting a second subject image in which motion blur is removed from the first subject image according to point spread functions for each color channel modulated by the optical coded pattern set.